ANALISIS STRATEGI PEMASARAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) NYONYA SAMBEL KECAMATAN PAMIJAHAN, KABUPATEN BOGOR DALAM PERSPEKTIF MANAJEMEN SYARIAH - Nining Yulia Anggraeni; Susi Melinasari; Hasbi Ash Shiddieqy (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2022)
The marketing elements contained in every MSME business actor (Micro, Small and Medium Enterprises) include maintaining a quality product (product), the right price (price), attractive promotion (promotion), as well as a strategic location (place). The competition is so tight that the UMKM Nyonya Sambel must be superior compared to its competitors. Therefore, the marketing strategy plays an important role in determining the survival or failure of a business. This study aims to analyze a good and appropriate marketing strategy for Mrs. Sambel UMKM, Pamijahan District, Bogor Regency and in line with sharia management principles. The research used a descriptive qualitative method using Strengths Weaknesses Opportunity Threats (SWOT) analysis and took place at the UMKM of Nyonya Sambel, Pamijahan District, Bogor Regency. The results of this study indicate that Mrs Sambel's SMEs apply the components in the marketing strategy, namely Segmenting, Targeting, Positioning. UMKM Nyonya Sambel also formulates a 4P marketing mix strategy, Product, Price, Place, Promotion. In addition, there is conformity with sharia management principles, namely the principle of amar ma'ruf nahi munkar, the obligation to uphold the truth, the obligation to uphold justice and also the obligation to convey the mandate. Based on the results of the SWOT analysis, Mrs. Sambel's UMKM is in quadrant I Growth (development), meaning that this position is a very profitable situation and continuous improvement is still needed.